Avaliação do ciclo de vida da produção de bioetanol a partir de resíduos alimentares - Fagundes, Victória Dutra (2023)
Large amounts of food waste are generated worldwide and its disposal is currently becoming a challenge. Food waste is considered an ideal raw material for the production of biofuels, particularly bioethanol, due to its composition. The bioethanol production process consists of the steps of pretreatment, enzymatic hydrolysis, fermentation and product recovery. However, there is still a need for studies aimed at evaluating the possible impacts generated by the production of bioethanol from food waste. For this, the most common tool for evaluating the environmental performance of a process or product is the Life Cycle Analysis (LCA). The present work aims to perform the LCA of bioethanol produced from food waste, and the work is divided into two main stages in which the methodology used was carried out following the steps established by ISO 14.040 (2006). The Ecoinvent vs. 3.4 was used to insert inventory data into the SimaPro 8.5.0.0 software, which was used for the environmental impact assessment stage using the ReCiPe method (midpoint and endpoint) and to validate the LCA methodology through uncertainty analysis using the Monte Carlo method. In the first stage, the LCA of bioethanol production from banana, potato and papaya waste was carried out in three process stages (pre-treatment, enzymatic hydrolysis and fermentation) evaluating the process considering the energy consumption per equipment and not considering the energy consumption. It was concluded that fermentation is responsible for the greatest number of impacts and environmental damages when considering energy consumption, when not considering energy consumption, the greatest impacts and damages are related to the pre-treatment stage for all waste. Of the 18 impact categories evaluated, the impact categories that contribute most to the generation of impacts are: global warming potential (GWP), terrestrial ecotoxicity (TTE) and scarcity of fossil resources (SFR). For the damage categories, the most representative was Resources. Bioethanol production from banana waste is the process that generates the most impacts and environmental damages, when compared to potato and papaya waste. In the second stage of the dissertation, the LCA of bioethanol production from blends of potatoes, fruits and industrialized foods was carried out in three process stages (pre-treatment, enzymatic hydrolysis and fermentation + distillation). For this stage, two scenarios were proposed, one with the common process (Scenario 1) and another optimized scenario (Scenario 2), in which the drying process and replacement of phosphate buffer by citric acid were removed, both scenarios were evaluated considering the energy consumption in the process of obtaining bioethanol and not considering the energy consumption in the process. As a conclusion, fermentation represented the greatest impacts and environmental damage for all scenarios evaluated when considering energy consumption, when not considering energy consumption, the pretreatment stage represented the greatest impacts and environmental damage also for all scenarios evaluated. The PAG, ETT and ERF represented the impact categories with the greatest associated impacts, respectively, and the Resources damage category represented the greatest associated damage for all scenarios evaluated. The optimized scenario presented lower impacts and environmental damage when compared to the common scenario for all blends, being an option for environmental improvements for the bioethanol production process.